Strenghening Anemia Prevention Among Adolescent in Timor Leste : A Systematic Review - Joaninha Cavalho de Jesus; Delmi Sulastri (Jurnal Ners, 2025)
Abstract Anemia remains a significant public health concern in Timor-Leste, particularly among adolescents, primarily due to rapid developmental changes and inadequate nutrition. Its impact includes fatigue, diminished concentration, and lowered immune function. Promoting nutritional awareness among teenagers can lead to healthier eating habits, increased iron consumption, and better adherence to supplement regimens. Supplementing with iron and folic acid has proven effective in preventing iron deficiency and supporting proper growth. Enhancing education about nutrition is vital in mitigating anemia and fostering both academic performance and overall adolescent well-being.A systematic review was conducted in line with PRISMA guidelines, using databases such as PubMed, Google Scholar, and Science Direct to locate pertinent studies. The review focused on empirical investigations that aimed to improve adolescent anemia prevention, utilizing qualitative, quantitative, or mixed-method approaches. From an initial pool of 568 studies, 10 met the eligibility requirements and were included in the final synthesis. Key findings emphasized the critical role of nutrition education and the consistent use of iron supplements. The review also highlighted the need for future studies to concentrate on strategies that enhance long-term adherence.